Efficient Spin‐Direction Coupling between Circular Polarized Electric and Magnetic Dipoles and Photonic Modes. Issue 2 (14th December 2022) - Zhai, Tingting; Mazzola, Matteo; Macias, Demetrio; Salas‐Montiel, Rafael
Abstract: Integrated single photon sources are essential elements in quantum computing, simulation, communication, and photonic neural networks. The directional radiation and scattering of single‐photon sources play a crucial role in light manipulation and rely on electric and magnetic dipole moments. Although clever physical insights and designer intuition strategies have been successfully applied in the development of integrated sources, inverse strategies could enhance and maximize its performance. Recently, topology‐optimized couplers for on‐chip single‐photon sources are designed to efficiently couple a guided mode and an electric dipole. However, the superposition of orthogonal electric and magnetic dipoles can also be harnessed due to the additional degrees of freedom via their interference. Here, the authors have extended the strategy to couplers that enhance spin‐direction coupling of circularly polarized, Huygens, and Janus dipoles. The authors demonstrate that optimization not only increases the coupling to a desire mode but also enhances the electric and magnetic local density of states (LDOS) while maintaining the amplitude and phase relation between the orthogonal dipoles for unidirectional coupling. Currently, coupling efficiency and enhanced LDOS of up to 88%, 94%, and 93% and up to 9.4, 18.6, and 14.9 are obtained for these dipoles. The topology optimization improves the performances of 3D integrated photonic devices. Abstract : Integrated couplers that enhance spin‐direction coupling between circular polarized electric and magnetic dipoles and photonic modes are demonstrated. The topology‐optimized nanophotonic devices not only increase the light coupling to a desire mode but also enhance the electric and magnetic local density of states. Currently, coupling efficiency of more than 90% is obtained for the circular polarized, Huygens, and Janus dipoles.